2010
DOI: 10.1007/s11846-010-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of voluntary CSR disclosure: empirical evidence from Germany

Abstract: Currently, companies spend a great deal of effort on Corporate Social Responsibility (CSR) disclosures. CSR disclosure relates to the provision of information on companies' environmental and social performance. From an economic perspective, companies might disclose this information to avoid or decrease potential political costs. We construct a CSR disclosure index based on the Global Reporting Initiative (GRI) guidelines. Using content analysis, we analyze 130 listed German companies' CSR disclosures (470 firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
691
7
65

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 708 publications
(891 citation statements)
references
References 84 publications
61
691
7
65
Order By: Relevance
“…This paper extends prior research on the effect of company-level determinants in explaining voluntary CSR disclosure practices (Lan, et al, 2013;Gamerschlag et al, 2011). The study will address two fundamental research questions: 1) What are the company-specific characteristics associated with corporate social responsibility (CSR) disclosures?…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…This paper extends prior research on the effect of company-level determinants in explaining voluntary CSR disclosure practices (Lan, et al, 2013;Gamerschlag et al, 2011). The study will address two fundamental research questions: 1) What are the company-specific characteristics associated with corporate social responsibility (CSR) disclosures?…”
Section: Introductionmentioning
confidence: 74%
“…Despite the increased CSR awareness among Malaysian companies and noteworthy efforts to go beyond the standard industry and Bursa Malaysia reporting requirements, the quality of CSR disclosures within Malaysian annual reports is dismal to the normal scope of corporate financial reporting (MaSRA, 2013). Previous studies have suggested the importance of company-specific characteristics as proxies in inducing their disposition and responsiveness in disclosing additional CSR information voluntarily (Lan et al, 2013;Gamerschlag et al, 2011;Siegel and Vitaliano, 2007;Orlitzky et al, 2003). Thus, this study seeks to determine the pre-existing influence of company-level variables on the level of sustainability reporting preceding the transitional implementation period of the G4 Sustainability Reporting Guidelines in 2014 and 2015. In addressing the internal organisational factors of sustainability reporting, extensive literature search indicated dearth of quantified measures on board experience as an antecedent to CSR disclosure levels.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Guthrie and Abeysekera (2006) and Gamerschlag et al (2011) emphasize that selection of a "unit of analysis" presents another critical issue in the process of measuring the extent of environmental disclosure through content analysis. In this respect, Holsti (1969) p. 116 defined recording unit as "the specific segment of content that is characterized by placing it into a given category" (Holsti 1969).…”
Section: Samplementioning
confidence: 99%
“…In this respect, Holsti (1969) p. 116 defined recording unit as "the specific segment of content that is characterized by placing it into a given category" (Holsti 1969). As the number of words in a recording unit has the advantage of being categorized more easily (Damak-Ayadi 2010) and needs less subjective judgment by the researcher (Gamerschlag et al 2011), the extent of environmental disclosures is measured by counting the number of words related to the environmental disclosure. Table 2 summarizes the measurement of the independent variables used in this study.…”
Section: Samplementioning
confidence: 99%